Students’ attitude-behavior gap on issues of labor exploitation - Hiller Connell, Kim Y.; Kozar, Joy M. (International Textile and Apparel Association, Inc., 2011)
A study by Kim and Damhorst (1998) found that, despite holding attitudes of environmental concern, only a limited degree of socially responsible apparel consumption behaviors were present among apparel consumers. The present study seeks to examine further the relationship between consumers’ knowledge and attitudes of labor exploitation issues in the production and distribution of apparel goods and their apparel purchasing decisions.
Keywords: Purchase behavior; Social responsibility; Sweatshops; College students